Age and diversity of Mediterranean dwarf shrublands: a dendrochronological approach along an altitudinal gradient on Crete. (12th March 2013) - Zimowski, Mateusz; Leuschner, Hanns H.; Gärtner, Holger; Bergmeier, Erwin; Pillar, Valério
Abstract Questions To what extent do Mediterranean dwarf shrub species of phrygana and mountain habitats form distinct annual growth rings and are therefore suitable for further studies on the dynamics of phrygana? How are growth ring numbers and species turnover of dwarf shrub communities distributed along an altitudinal gradient of ca. 1800 m? Is the age distribution of dwarf shrub populations in high‐mountain areas different from that in the lowlands? Which environmental factors control the beta‐diversity of East Mediterranean dwarf shrub species and communities? Location Lefka Ori (western Crete, Greece). Methods Plots of 100 m2 at different altitudes were sampled for (1) composition of dwarf shrub species and environmental variables, and (2) wood samples of the root collar of all 24 phryganic dwarf shrub species occurring in the plots. Thin discs were cut, and in order to visualize cells and ring structure, surfaces were handled with razor blades. Additional cross‐sectional micro‐sections were cut with a sledge microtome. Growth rings were counted and box‐plotted in correlation with the altitudinal gradient. Beta‐diversity and environmental variables were analysed using gradient analyses. Results Most dwarf shrubs showed species‐specific distinct growth rings, and are accordingly suitable for age‐structure analyses and further research on the functional dynamics of phrygana. The oldest dwarf shrubs were found at high altitudes. Factors controlling beta‐diversity and species composition of dwarf shrublands were altitudinal and edaphic. Conclusions Growth ring analysis proved useful for age determination of Mediterranean dwarf shrubs. Our results show that dwarf shrub communities at higher elevations are older than those at low elevations, perhaps a general principle in plant ecology that is confirmed here for the East Mediterranean phrygana.